Experiencing Communication Through Youtube Membership: A Phenomenological Study on The Deankt Community - Dimaz Rahmadhi; Tri Widya Budhiharti; Nurkinan Nurkinan (INFOKUM, 2025)
YouTube Membership is a monetization feature that not only provides financial benefits for content creators but also facilitates exclusive communication spaces between creators and audiences. Amid the growing trend of digital participation in Indonesia, it is important to examine how users experience and interpret interactions within such digital communities. This study explores how audiences engage in communication through the YouTube Membership feature, focusing on the DEANKT channel. Using Alfred Schutz’s phenomenological approach, it investigates both the "because motives" (past experiences) and "in order to motives" (future expectations) behind users’ decisions to subscribe. Data were gathered through in-depth interviews and participant observation with six long-term members of the DEANKT community. The findings reveal that key motivations include emotional attachment to the creator, access to exclusive content, and the desire for a sense of belonging in a digital community. Concretely, members reported intimate and personalized interactions such as name mentions during live streams, use of visual symbols like badges and emojis, and active participation in closed forums such as Discord. These interactions fostered emotionally fulfilling and participatory communication experiences that also reinforced members’ digital identities. This study underscores that YouTube Membership serves a dual role—not only as a monetization tool but also as a powerful medium for building meaningful and tightly connected digital communities.